STRATEGI BISNIS DALAM MENINGKATKAN DAYA SAING PADA TOKO MANDIRI JAYA ABADI MEDAN - Mario Andrias Kiton; Michael Novranda Surbakti; Nicolas (Halu Oleo University, 2024)
The building materials distribution industry is one of the economic sectors that continues to grow in line with the development and renovation in various sectors, including property and construction. The demand for building materials continues to increase with the improvement of the property and construction sectors during the post-pandemic recovery period. This study aims to formulate strategies to enhance competitiveness at Toko Mandiri Jaya Abadi Medan using SWOT analysis. In conducting this research, the researcher employed SWOT analysis with a descriptive qualitative approach to illustrate the internal and external factors of Toko Mandiri Jaya Abadi Medan. Data collection was carried out through observation and interviews with the store owner and customers. The results of this study indicate that it is necessary to implement strategies that utilize internal strengths to exploit external opportunities and reduce weaknesses by anticipating threats for the advancement of Toko Mandiri Jaya Abadi Medan.